Reproduction, Chromosome Number, and Postembryonic Development of Panagrellus redivivus (Nematoda Cephalobidae) - Hechler, H C (Journal of nematology, 1970)
Panagrellus redivivus (L.) T. Goodey reproduced amphimictically; the sexual primordia of males had nine chromosomes, those of females had ten. Eggs contained five chromosomes, sperm four or five. There were four molts, all after hatching. The sexes could be separated at the second molt by development of a lobe of somatic cells in the gonad, anteriorly in males, posteriorly in females. The lobe in males reflexed posteriorly at the third molt and joined the rectum at the fourth molt. Third molt females had a thickened vaginal primordium and at the fourth molt the spermathecal and uterine primordia were evident. The uterus elongated enormously in the adult. The 15 ventral chord nuclei between esophagus and rectum in the first stage increased to approximately 63 during the first molt; specialized nuclei, not evident until the third molt, participate in vaginal lining formation in fourth molt females. Sperm were first produced at the late fourth molt. Eggs, not produced until after copulation, hatched within the uterus